KRAS pathway expression changes in pancreatic cancer models by conventional and experimental taxanes - Oliverius, M; Flasarova, D; Mohelnikova-Duchonova, B; Ehrlichova, M; Hlavac, V; Kocik, M; Strouhal, O; Dvorak, P; Ojima, I; Soucek, P (Mutagenesis, 2019)
The KRAS signalling pathway is pivotal for pancreatic ductal adenocarcinoma (PDAC) development. After the failure of most conventional cytotoxic and targeted therapeutics tested so far, the combination of taxane nab-paclitaxel (Abraxane) with gemcitabine recently demonstrated promising improvements in the survival of PDAC patients. This study aimed to explore interactions of conventional paclitaxel and experimental taxane SB-T-1216 with the KRAS signalling pathway expression in in vivo and in vitro PDAC models in order to decipher potential predictive biomarkers or targets for future individualised therapy. Mouse PDAC PaCa-44 xenograft model was used for evaluation of changes in transcript and protein levels of the KRAS signalling pathway caused by administration of experimental taxane SB-T-1216 in vivo. Subsequently, KRAS wild-type (BxPc-3) and mutated (MiaPaCa-2 and PaCa-44) cell line models were treated with paclitaxel to verify dysregulation of the KRAS signalling pathway gene expression profile in vitro and investigate the role of KRAS mutation status. By comparing the gene expression profiles, this study observed for the first time that in vitro cell models differ in the basal transcriptional profile of the KRAS signalling pathway, but there were no differences between KRAS mutated and wild-type cells in sensitivity to taxanes. Generally, the taxane administration caused a downregulation of the KRAS signalling pathway both in vitro and in vivo, but this effect was not dependent on the KRAS mutation status. In conclusion, putative biomarkers for prediction of taxane activity or targets for stimulation of taxane anticancer effects were not discovered by the KRAS signalling pathway profiling in various PDAC models.
Keywords: nádorové buněčné linie; paclitaxel; signální transdukce; taxoidy; Gemcitabine; přemostěné cyklické sloučeniny; Bridged-Ring Compounds; transkriptom; Carcinoma, Pancreatic Ductal; Deoxycytidine; albuminy; Taxoids; Signal Transduction; nádory slinivky břišní; Mice; Cell Proliferation; Cell Line, Tumor; Transcriptome; duktální karcinom slinivky břišní; Biomarkers, Tumor; Albumins; Mice, Nude; ženské pohlaví; nádorové biomarkery; zvířata; Humans; deoxycytidin; Pancreatic Neoplasms; myši nahé; myši; Antineoplastic Combined Chemotherapy Protocols; proliferace buněk; gemcitabin; Proto-Oncogene Proteins p21(ras); protokoly protinádorové kombinované chemoterapie; protoonkogenní proteiny p21(ras); Female; Paclitaxel; lidé; Animals